Types of personality motivation structure of women who are acquiring higher education in psychology - PARTYKO, TETIANA (Journal of Education Culture and Society, 2020)
The article deals with the results of empirical research on the types of personality moti-vation structure of women who are acquiring higher education in psychology. Two types have been singled out: expressive and impulsive. The expressive type comprises two com-ponents: ideal motivation aimed at life necessities, general activity and social utility, and real motivation aimed at comfort, social status and communication. In the structure of the impulsive type there are three components: real motivation aimed at life necessities, so-cial status, general activity and social utility; real motivation aimed at communication and comfort; creativity motivation aimed at self-development and creative activity. Women belonging to the expressive type of personality motivation structure have more positive self-attitude and a higher level of psychological well-being than women belonging to the impulsive type.